Hubungan Status Gravida, Usia, BMI (Body Mass Index) dengan Kejadian Preeklampsia - Arwan, Berriandi; Sriyanti, Roza (Andalas Obstetrics And Gynecology Journal, 2020)
Background: Preeclampsia is one of the complications in pregnancy that can cause serious illness, long-term disability, and death in the mother, fetus and neonate. There are many risk factors that influence the occurrence of preeclampsia, such as primigravida, hyperplasentation, extreme maternal age (less than 20 years and more than 35 years), family history of preeclampsia / eclampsia, kidney disease, diabetes mellitus, chronic hypertension that has happened before pregnancy (less than 20 years and more than 35 years), family history of preeclampsia / eclampsia, kidney disease, diabetes mellitus, chronic hypertension that has been suffered before pregnancy (less than 20 years and more than 35 years). superimposed preeclampsia) and obesity. Objective: To determine the relationship between gravida status, age, and BMI status with the incidence of preeclampsia.Methods: The descriptive analytic study was using a cross sectional study design by looking at the medical records of subjects according to the time and place of research. The study population was all medical records of pregnant women with preeclampsia and those without preeclampsia in the Department of Obstetrics and Gynecology Dr. M. Djamil Padang period 1 January 2017 - 31 December 2017. Samples were taken from populations that met the inclusion criteria and did not have exclusion criteria. Sampling using consecutive sampling techniques was taken from the Medical Record Section of RSUP Dr. M. Djamil Padang. Univariate analysis was used to assess gravida status, maternal age, and BMI. Bivariate analysis was performed using the chi square test with a significance level of p <0.05.Results: A total of 63.7% of patients with severe preeclampsia were primigravida (p <0.05), 52.5% were high risk groups with age <20 years and> 35 years (p <0.05), and 55% of patients with overweight and obese group (p <0.05). Primigravida has a tendency to suffer from preeclampsia compared to multigravida. Patients who have a tendency for preeclampsia are patients with overweight and obese BMI status with a high risk age range.Conclusion: There is a significant relationship between gravida status, age, and BMI to the incidence of preeclampsia. Keywords: gravida, age, BMI, preeclampsia